2021
DOI: 10.52113/mjas04/8.3/44m
|View full text |Cite
|
Sign up to set email alerts
|

Some genetic parameter for maize under different planting dates and environments

Abstract: "To evaluate the performance of introduced varieties of maize under different sowing dates and locations, in addition to local variety, a field experiment was carried out in two locations;. The study compared five varieties of maize introduced from America, with a local synthetic variety (Ibba 5018) and tested it in two locations at three sowing dates (1, 15 July and 1 August). The Randomized Complete Block Design RCBD was used with four replications, with spilt plot arrangements, the main plots included three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
3
3
0
Order By: Relevance
“…The variation in flowering time among the single cross hybrids and their parents is attributed to genetic diversity, reflecting differences in morphological traits and their response to environmental factors such as temperature and photoperiod, resulting in differences in the number of days required to reach tasseling. This finding is consistent with previous studies [7], [8], and [9], which also found significant differences among triple hybrids in days to tasseling.…”
Section: Number Of Days From Planting To 75% Tasseling (Days)supporting
confidence: 94%
See 1 more Smart Citation
“…The variation in flowering time among the single cross hybrids and their parents is attributed to genetic diversity, reflecting differences in morphological traits and their response to environmental factors such as temperature and photoperiod, resulting in differences in the number of days required to reach tasseling. This finding is consistent with previous studies [7], [8], and [9], which also found significant differences among triple hybrids in days to tasseling.…”
Section: Number Of Days From Planting To 75% Tasseling (Days)supporting
confidence: 94%
“…The superiority of parent 5 in the number of grain rows can be attributed to its superiority in both the traits of number of ear rows and number of grains row -1 (Table 5 and 6). Similarly, the superiority of the hybrid (5×1) can be attributed to its superiority in the trait of number of grains row -1 (Table 6), this aligns with findings from previous studies [29][30][31].…”
Section: Number Of Grains Ear -1supporting
confidence: 91%
“…The difference in the number of leaves between dates may be due to the difference in plant height (table, 6). [6,25,31,32,33], reached similar results. The results of Table 6 showed that there was no significant effect of plant densities on the number of leaves, while the varieties differed in the number of leaves, as the Egyptian variety TW-345 excelled by giving the highest rate (14.63) leaves per plant, significantly different from all the Iraqi and Egyptian varieties used, while the Iraqi variety gave AL-Maha had the lowest rate of (12.72) leaf plant -1 .…”
Section: Number Of Active Leaves (Plant Leaf -1 )supporting
confidence: 64%
“…43.9%, for two traits of plant height and ear height. [11] noted in his study of some genetic parameters in the two locations of Baghdad and Diyala under three planting dates, that the genetic variance is higher than the environmental variance for most traits, and that the phenotypic variance coefficient is close to the genetic variance coefficient, and this indicates that the studied traits are genetically controlled and that the influence of environmental factors is small.The study aimed to estimate the genetic parameters and heritability of double crosses maize under planting dates suitable for fall season in Iraq.…”
Section: Introductionmentioning
confidence: 95%